EU-African regional trade agreements as a development tool to reduce EU border rejections - Dela-Dem Doe Fiankor; Malte Ehrich; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
The integration of developing countries into the world trading system is an important development mechanism to reduce poverty in these countries. Regional Trade Agreements (RTAs) have recently spread in terms of quantity and type. Some of these, like the Economic Partnership Agreements (EPAs) differ from previous RTAs as they explicitly support export capacities of developing countries. Therefore, it is particularly relevant to investigate the effect of eligibility for various types of RTAs first on exports and second on rejections at EU borders. Empirical analysis is carried out on 52 African countries' exports of fruits, nuts and vegetables and fish to the EU-27 from 2008 to 2013. Adopting the gravity framework we find that only EBA eligibility has induced significantly exports of fruits, nuts and vegetables from Africa to the EU-27. Estimating different count models using border rejection data from the EU Rapid Alert System for Food and Feed database, we also find other trade enhancing effects of RTAs that go beyond tariff reductions, as all EU-Africa RTAs have negative effects on border rejections. The effects nevertheless differ across agreements and products. Specifically, EPA eligibility decreases rejections on both products, GSP decreases rejections on fish and fish products and FTA (TDCA and Euro-Med) decreases rejections on fruits, nuts and vegetables.
Keywords: F13; F14; F15; Q17; 330; Agricultural trade; Border rejections; Regional trade agreements; Africa